Problems of national education: historical retrospective (on the example of I.D. Popko's activity) - Trofimenko S. V. (Interactive science, 2019)
the difficulties of public education have not lost their relevance today. Vivid personalities served and serve as substantial support in the matter of education. This article raises the question of the development of public education in the Kuban region, as well as the influence of the outstanding enlightener Lieutenant General I.D. Popko on this process. Having conducted a historical analysis of the personal library of the Kuban figure, the authors define the goals, chronological and territorial frameworks of the educational activities of Ivan Diomidovich. The basis of the study was the catalog left by I.D. Popko in a noble house in the city of Stavropol, as well as in the work of I.V. Dubinin and I.G. Ivantsov «Materials for the bibliographic reconstruction of the catalog of the personal library of Ivan Diomidovich Popko» [8].
Keywords: Кавказ; Ставропольский край; просветительская деятельность; educational activities; Попко; Кубанская область; Черноморское казачье войско; личная библиотека; Popko; Caucasus; Kuban region; Stavropol Territory; Black Sea Cossack army; personal library